THE RESCUING PROCESS OF WOMEN'S SELF CAREWITHIN A CONTEXT OF DOMESTIC ABUSE - Leila Platt Deeke; Elza Berger Salema Coelho; Antonio Fernando Boing (Universidade Federal do Paraná, 2007)
This article presents a study on the rescue process of self care with women in a domestic violence context. This proposalwas developed by means of a caring practice justified by the interest in carrying out selective prevention from drug abuse and directedto six women submitted to domestic abuse. The data collection was effected through a semi-structured interview, from March to Mayof 2004 and analyzed according to two thematic axles proposed by Bardin: 'Knowing the other through listening' and 'self care throughdialogue'. Those women take ansiolitics in order to cope with the psychological distress and expecting to reduce the negative emotionstriggered by violence. It was important encourage such women in the identification of risk behaviors and situations as well as the drugfunctions in that context of domestic abuse.